UPAYA GURU BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI MELALUI TEKNIK REWARD DI SMK BROADCASTING BINA CREATIVE MEDAN - Nurul Fadillah (UIN Sumatera Utara, 2020)
The research was carried out at Broadcasting Bina Creative MedanVocational High School. The purpose of study is (1) know student learningoutcomes before using reward techniques, (2) know student outcomesafter using reward techniques, (3) inhibiting and supporting factors toimprove student learning outcomes through reward techniques.this typeresearch is guidance and counseling action research. Data collectionprocedures in this study were observation and interviews. This researchinstrument is to use an observation sheet. The data technique used isqualitative analysis. Based on research that has been done, the resultsobtained are: 1).Learning outcomes that exist in class XI Students oVocational High School BBC Medan TA. 2018/2019 before attending groupguidance services with the reward technique tends to be low. 2). Theimplementation of group guidance services with reward techniques toimprove student learning outcomes has a significant effect. 3). From theresult of the study it can be concluded that before the action of groupguidance with reward techniques, student learning outcomes in the lowcategory. After being given group guidance services with a rewardtechnique in the first cycle with two meetings with moderate result and inthe second cycle with two meetings getting good results or increasing.Keyword : Learning Outcomes, Reward Technique